(untitled) (Journal of Social Sciences Review, 2023)
The utilization of soft power, based on attraction and persuasion, is crucial for countries in the international arena, as it discourages the use of hard power. For China, soft power is just as pivotal as hard power in its efforts to dominate the world. Beijing’s preoccupation with soft power is rapidly increasing, and it seeks to convince the world that it is a benign power and believes in soft power in foreign policy. China has now emerged as a rising power due to its strong economy, initiation of the Belt and Road Initiative BRI, the resolution of outstanding issues with neighboring states, rapid progress in technological development, and contribution to UN peacekeeping missions. Despite this, China’s image in the West is not positive, and the US and its allies will continue to attempt to damage China’s soft power image by criticizing its BRI, debt-trap policies, authoritarian regime, human rights violations, and labor exploitation in Africa. The competition for soft power dominance between the US and China is in full swing. Both states seek to continue their hegemony in the 21st century. Therefore, this paper aims to analyze and compare the utilization of soft power by China and the US, highlighting their respective soft power strategies.